Respuesta :
Answer:
6=−3−6
Step-by-step explanation:
6=-3(x+2)
6=-3x-6
[tex]\text {Hello! Let's Solve this Problem!}[/tex]
[tex]\text {\underline {The First Step is to Flip The Equation}}[/tex]
[tex]\text {Before: 6= -3(x+2)}\\\text {After: -3(x+2)=6}[/tex]
[tex]\text {\underline {The Next Step is to Simplify the Equation}}[/tex]
[tex]\text {-3*x=-3x}\\\text {-3*2=-6}[/tex]
[tex]\text {Your New Problem Should Be: -3x-6=6}[/tex]
[tex]\text {\underline {The Next Step is to Add 6 to Both Sides}}[/tex]
[tex]\text {-3x-6+6 (-6+6 crosses out because it'll equal 0}\\\text {6+6=12}[/tex]
[tex]\text {To get x by itself we must divide now}[/tex]
[tex]\text {\underline {The Final Step is to Divide Both Sides by -3}}[/tex]
[tex]\text {-3x/-3=0 (this crosses out each other. Leaving x by itself)}\\\text {12/-3=}[/tex]
[tex]\text {Your Answer Would Be:}[/tex]
[tex]\huge\boxed {x=-4}[/tex]
[tex]\text {Best of Luck!}[/tex]